2023
DOI: 10.3389/fnagi.2023.1156764
|View full text |Cite
|
Sign up to set email alerts
|

The role of sex differences in depression in pathologically defined Alzheimer’s disease

Abstract: IntroductionSex differences in Alzheimer’s disease (AD) may contribute to disease heterogeneity and affect prevalence, risk factors, disease trajectories and outcomes. Depression impacts a large number of patients with AD and has been reported to be more prevalent in women. We aimed to better understand the interaction between sex, depression and AD neuropathology, which could have implications for detection of symptoms, earlier diagnosis, therapeutic management, and enhanced quality of life.MethodsWe compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…AD represents the most prevalent form of dementia, and nearly all patients experience neuropsychiatric symptoms, with depression being one of the most common psychiatric disorders, in conjunction with cognitive and memory deficits ( Lyketsos et al, 2011 ; Santos et al, 2016 ; Depp et al, 2023 ; Rodriguez Salgado et al, 2023 ; Tremblay et al, 2023 ). Importantly, depression not only manifests as an early symptom of AD dementia but also increases the risk of AD, and conversely, depressive disorders can also arise in response to cognitive decline due to AD ( Elser et al, 2023 ; Liao et al, 2023 ), suggesting a crucial and bidirectional association between AD and depression.…”
Section: Sex Differences In the Relationship Between Ad And Depressionmentioning
confidence: 99%
See 3 more Smart Citations
“…AD represents the most prevalent form of dementia, and nearly all patients experience neuropsychiatric symptoms, with depression being one of the most common psychiatric disorders, in conjunction with cognitive and memory deficits ( Lyketsos et al, 2011 ; Santos et al, 2016 ; Depp et al, 2023 ; Rodriguez Salgado et al, 2023 ; Tremblay et al, 2023 ). Importantly, depression not only manifests as an early symptom of AD dementia but also increases the risk of AD, and conversely, depressive disorders can also arise in response to cognitive decline due to AD ( Elser et al, 2023 ; Liao et al, 2023 ), suggesting a crucial and bidirectional association between AD and depression.…”
Section: Sex Differences In the Relationship Between Ad And Depressionmentioning
confidence: 99%
“…Notably, both depression and AD display a significant sex disparity, with a higher prevalence observed among women ( Wang et al, 2022a ), but existing research on sex differences in the association between AD and depression produces incongruent findings. A recent study noted men appearing to be more susceptible to developing depressive symptoms following the onset of AD ( Tremblay et al, 2023 ), which may arise from overlapping symptoms between AD dementia and depression, as well as the absence of consensus criteria to diagnose AD-related depression. Likewise, another study revealed that men diagnosed with depression have a higher risk of developing AD ( Elser et al, 2023 ), but men may be less inclined to seek healthcare compared with women, resulting in consistent underestimation of the prevalence of depression among men.…”
Section: Sex Differences In the Relationship Between Ad And Depressionmentioning
confidence: 99%
See 2 more Smart Citations